Classical sociological theory : a reader - McIntosh, Ian, 1960- (Edinburgh University Press, 1997)
A generous set of readings taken from Marx, Weber and Durkheim, deliberately lengthy to impart a full understanding of the text, are the basis of this reader that is aimed at 1st and 2nd year undergraduate students of sociological theory and social theory.